1996
DOI: 10.1055/s-2007-1005601
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Surveillance in Ulcerative Colitis: A Survey of Patients' Knowledge

Abstract: Large numbers of patients are unaware of the existence of screening facilities for colorectal cancer, and are ignorant of the treatment of the disease. Increased public information is required to improve compliance with screening programmes, and to enable patients to take part in decisions about their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Robinson et al found that inadequate patient education and information may account for the problems of poor compliance in cancer surveillance programs. 28 The patients who participated in our surveillance program seemed to be well informed and were compliant to the program. The overall results from the current study are further supported by preliminary data from another Swedish study, showing that a group of 78 UC patients undergoing surveillance had better psychologic well‐being than normal controls and had high confidence in colonoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Robinson et al found that inadequate patient education and information may account for the problems of poor compliance in cancer surveillance programs. 28 The patients who participated in our surveillance program seemed to be well informed and were compliant to the program. The overall results from the current study are further supported by preliminary data from another Swedish study, showing that a group of 78 UC patients undergoing surveillance had better psychologic well‐being than normal controls and had high confidence in colonoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Robinson et al demonstrated that 86% of UC patients were aware of the increased risk of CRC. 16 Siegel et al showed that 91% of patients recognized that UC was associated with a risk of CRC. 17 And according to Baars et al's study, approximately three-quarters of IBD patients thought that the risk of CRC was high.…”
Section: Discussionmentioning
confidence: 99%
“…Another study, however, did not find such a high level of knowledge. 16 However, two-thirds of patients were not aware of the frequency of screening. This is not surprising, since several researches have demonstrated that most gastroenterologists practice surveillance on a disorganized basis.…”
Section: Discussionmentioning
confidence: 99%
“…Eaden et al 93 found that most endoscopists did not comply with the recommended number of biopsies, and only 53% recommended colectomy when high-grade dysplasia was found in the specimens. Patient surveys94 have highlighted that a proportion of patients were unaware of the need for surgery should carcinoma be found on screening. Lynch et al 95 have questioned the overall benefit of the surveillance programme in detecting and preventing deaths from colorectal cancer.…”
Section: Screeningmentioning
confidence: 99%